Emerging corticosteroid resistance: Need for customized medication based on pharmacogenomics profiling - Navakanth Raju Ramayanam, Rajeshan Nanda Amarnath, Mohan Kumar Ramasamy, Thangavel Mahalingam Vijayakumar (Journal of Applied Pharmaceutical Science, 2023)
Most of the prescribed drugs for inflammatory illnesses are corticosteroids. Since the majority of patients obtain maximum remission with corticosteroid treatment, glucocorticoids seem to have been the bedrock of treating inflammatory disorders for decades. The clinical signs of illness and harmful impacts of glucocorticoid therapy are presently most often standardized for the first manifestation and relapse of inflammatory disorders. Still, there is significant interindividual variance in the glucocorticoid treatment response. The principles of corticosteroids and the pharmacodynamics of steroids in diverse inflammatory disorders are discussed in this study. The significant interindividual heterogeneity in glucocorticoid response, however, need not be explained by these processes. Prior research has shown that genetic variables might significantly impact a patient’s and dynamic pharmacokinetic characteristics. As a result, pharmacogenetics may play an important role in customized medication for individuals suffering from inflammatory illnesses. The significance of gene variants on glucocorticoid responsiveness and steroid-related hazards in inflammatory disorders is still unknown. Although the evidence is limited, the results of this research imply that pharmacogenetics may improve glucocorticoid therapy individualization. To make an overall conclusion on the genetic impact of variants on glucocorticoid related hazards and eventually adopt pharmacogenetics in medical practice, bigger cohorts of patients with inflammatory illnesses are required.